Smart Parking System Based on Cloud Computing - Zubit, Muhammad Syazwan; Abdullah, Noorsaliza (Evolution in Electrical and Electronic Engineering, 2021)
Parking is an act of leaving a vehicle in a particular place for a period while parking system is the set of connected things or devices that can operate together in the systematic way. The problem that usually faces by Malaysia’s local authority council is a significant problem regarding the parking system. As we know the parking lot is important either in urban areas or in rural areas. This study aims to design and develop an application for a smartphone that would help the user and parking management to navigate the parking lot and to evaluate the functionality and the performance of the system and the application. At the end of the project, the user and the parking provider will have connected each other by an application for a better parking system solution. This project application can improve the effectiveness of the parking system. The application will help users to navigate, park and pay. The parking capacity, parking rate and parking time that was set up by the parking provider and stored in the firebase database of the application before being published to Playstore.